Analysis of High School Teacher's Biology Teacher's Perception on Biology Practice during the Covid-19 Pandemic in Rantauprapat City - Rina Solehawati; Novi Fitriandika Sari (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of this study was to find out the perception of high school biology teachers towards Biology Pratikum during the Covid-19 Pandemic in Rantauprapat City. This type of research uses quantitative with the method used is descriptive. The population of this research is 17 public high school teachers in Rantauprapat city with total sampling of 17 public high school teachers in Rantauprapat city. The data collection technique was carried out by giving a questionnaire to the teacher regarding the teacher's perception of the science practicum during the COVID-19 pandemic using the google form while the indicators in this study were (1) Ready to carry out the practicum; (2) Not ready to carry out practicum; (3) Not ready to carry out the practicum. The results of this study indicate that the indicator one Ready to carry out practicum scores 97.28%; Then the second indicator Not ready to carry out the practicum got a score of 82.22% and the third indicator Not ready to carry out the practicum got a score of 76.19%. In the end, the teacher stated that he still found it difficult to carry out practical activities during the Covid-19 Pandemic.